OPTIMIZATION Of E LEARNING THROUGH FEATURES GOOGLE FORM AND ADD TO INCREASE STUDENTS LEARNING EFFICIENCY - FAUZIH (JOSAR (Journal of Students Academic Research), 2021)
The purpose of this research is to develop online learning media (E-learning) which will be used in the lecture process with the help of a feature called Google Form and Add-On. This aims to provide an understanding, especially for teachers in the lecture process, so that assignments and examinations can be done online which can provide updated and fast results and reduce the cost of making assignments for students. The population of this study were all students of the S1 Study Program majoring in Management and Accounting at the Sekolah Tinggi Ilmu Ekonomi Enam Enam Kendari. Based on temporary data, the number of odd semester students is 857 students. The sampling technique in this research is using purposive sampling. In this study, a sample of 50 students representing each class of semester used online learning using the Google Form and Add-On features. This research method uses qualitative descriptive analysis techniques, namely by creating an online learning model to improve student learning efficiency using Google Form and Add-On in detail. The results showed that the use of online quizzes via google form and add-on really helped students in doing the assignments given because they could increase costs for students. In addition, with this online quiz, the process of checking the results of student answers is relatively fast because it does not require manual examination which takes a long time and helps teachers in giving assignments and learning more efficiently both in terms of time and from the aspect of cost. For further research, it is expected to be able to examine several applications and other online learning features that are useful in the learning process for students.